Demographic and Multimodal Imaging Features of Macular Telangiectasia Type 2: Korean Macular Telangiectasia Type 2 Study – Report No. 2. (3rd September 2021) - Kim, Young Ho; Chung, Yoo-Ri; Oh, Jaeryung; Kim, Seong-Woo; Lee, Christopher Seungkyu; Yun, Cheolmin; Lee, Boram; Ahn, So Min; Choi, Eun Young; Jang, Sungmin; Lee, Kihwang
ABSTRACT: Purpose : To investigate the demographic and multimodal imaging features of macular telangiectasia (MacTel) type 2 in Korea and their relationship with visual acuity and the clinical stage. Methods : A retrospective multicentre cross-sectional study was conducted in six tertiary hospitals in Korea and the study included 84 patients. Demographic data and imaging data of fundus photography, fundus autofluorescence (FAF), confocal blue-light reflectance (CBR), fluorescein angiography (FAG), and optical coherence tomography (OCT) were collected. Results : The Korean patients with MacTel type 2 were predominantly female (75%), and the mean logMAR visual acuity was 0.282 ± 0.280 at initial presentation. Most commonly presented signs were the loss of retinal transparency in fundus photographs (68.3%); increased autofluorescence in FAF (83.6%); increased blue reflectance involving the centre in CBR (68.0%); telangiectatic vessels in FAG (88.2%); and hyporeflective cavities in OCT (77.7%). The eyes diagnosed in the first half of the study period (2009–2014) showed a tendency to be diagnosed at more advanced severe stages than those diagnosed in the second half of the study period (2015–2019), using new severity scales based on FAG, FAF and OCT findings. Conclusion : The clinical features of MacTel type 2 in Korean patients assessed by newer imaging modalities suggest that Korean patients and the Caucasian-dominant population show similar presentations. This study showed that MacTel type 2 can be diagnosed in the earlier phase of the disease by using new imaging modalities and through better understanding of the disease.